2023
DOI: 10.1108/ijpdlm-07-2022-0236
|View full text |Cite
|
Sign up to set email alerts
|

Driving the talk: examining professional truck drivers' motivations to engage in eco-driving

Abstract: PurposeThis research examines what motivates professional truck drivers to engage in eco-driving by linking their self-reports with objective driving scores.Design/methodology/approachTheory of Planned Behavior (TPB) is illustrated in an embedded, single-case study of a Finnish carrier with 17 of its truck drivers. Data are obtained through in-depth interviews with drivers, their fuel-efficiency scores generated by fleet telematics and a focus group session with the management.FindingsDiscrepancies between dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Second, we found that a single, balanced safety and operations briefing before a dynamic driving task may not be enough to overcome drivers’ skill-related deficiencies to improve IRB. We acknowledge that this may be a factor of training or experience, or receiving one pre-task briefing may not have been enough to disrupt participants’ current habits to meet performance expectations (Jazairy et al. , 2023).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Second, we found that a single, balanced safety and operations briefing before a dynamic driving task may not be enough to overcome drivers’ skill-related deficiencies to improve IRB. We acknowledge that this may be a factor of training or experience, or receiving one pre-task briefing may not have been enough to disrupt participants’ current habits to meet performance expectations (Jazairy et al. , 2023).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…d. Improving vehicle routings to reduce the distances traveled, especially during delivery tours in urban areas [29][30][31]. e. Improving driver performance, e.g., eco-driving [32][33][34]. f. Platooning of trucks when traveling on motorways [35][36][37].…”
Section: Measures Specific For Freight Transportmentioning
confidence: 99%